Unemployment duration in Germany: individual and regional determinants of local job finding, migration and subsidized employment - Arntz, Melanie (Discussion paper, 2006)
Recent labor market reforms in Germany aim, among other things, at reducing unemployment by restricting passive unemployment measures, emphasizing local labor market policies and re-structuring public employment services. This paper uses extensive individual administrative and regional aggregate data to explore the extent to which these factors are likely to contribute to the shortening of unemployment duration. For this purpose, we estimate a semi-parametric duration model with three competing exit states. Our results suggest that changes in the unemployment compensation system rather than local employment policies and administrative restructuring efforts meet expected labor market outcomes. In addition, determinants of the length of unemployment vary across exit states.